(untitled) (Asian Journal of Medical and Biological Research, 2020)
The present study was to evaluate the reproductive and productive performance (RPP) of Indigenous (n=145) and Nili-Ravi cross-bred (n=55) dairy buffalo in relation to age, parity, body weight and body condition. A total of 200 buffalo cows were randomly selected and interviewed to collect data on reproductive and productive performance of buffalo cows of Rajshahi district by using pre-tested questionnaire during the period from January 2015 to December 2015. The average mean ± SD value of reproductive and productive performances were as age at puberty (AP), age at first calving (AFC), gestation length (GL), post-partum heat period (PPHP), milk yield per day (MYPD), lactation length (LL), birth weight of calf (BWC) and calving interval (CI) were recorded as 25.05±4.00 months, 35.26±4.14 months, 308.28±12.46 days, 84.00±25.95 days, 3.59±0.56 litre, 202.76±33.54 days, 28.79±4.23 kilogram and 461.36±15.41 days, respectively. Nili-Ravi cross-bred buffalo cow had shown better RPP than Indigenous. The genotype of buffalo cows had significant effect (p<0.05) on most of the RPP except AP, AFC and CI. Age of buffalo had also significant effect (p<0.05) on GL, PPHP and BWC and middle age (4 to < 7yrs) observed good RPP. The best RPP were recorded in 2nd parity than others and also significant effect (p<0.05) on GL, MYPD and BWC. Body weight and body condition of buffalo had significant effect (p<0.05) on PPHP, BWC and MYPD. The body weight of >350 kg and very good body condition groups were observed better reproductive performance. It could be concluded that the buffalo owners of these areas do not follow any scientific method of buffalo husbandry; they just follow traditional rearing systems. Very recently, a few farmers started farming of the mostly Indigenous buffalo cows for dairy purpose at Rajshahi region of Bangladesh. Asian J. Med. Biol. Res. September 2020, 6(3): 536-547